(untitled) (Journal of the Bangladesh Agricultural University, 2010)
The study estimates the growth rates of frozen food, shrimp and total export, and instability of export earnings. The study evaluates the export marketing of frozen food; shrimp and fish by using time series aggregated data from the year of 1972-73 to 2005-06. The growth rates of frozen food were 44%, 11%, and 10% during post-war period (1972- 73 to 1982-83), pre-trade liberalization (1983-84 to 1992-93) and post-trade liberalization period (1993-94 to 2005-06) respectively. The export growth rate of shrimp was 43% in post-war period and 13% and 12% in the pre-trade liberalization and post-trade liberalization period respectively. The overall estimated shrimp export growth was 19%. Total export earnings growth rate was much lower than shrimp growth rate in post-war period but it became higher in pre-trade liberalization and post-trade liberalization period. Export earnings including earnings from shrimp and frozen food was more stable in pre-trade liberalization period. Instability of export earnings from shrimp decreased markedly initially. It again increased in the recent past and the instability of shrimp export was lower than that of total export in all periods except post-trade liberalization period. The contribution of shrimp sector to total export earnings was 3.83% in 2005-06 and insignificant share of only 0.84% in the year 1972-73. The present circumstances of this sector demands different institutional supports significantly from different angles to strengthen the position in the international market and ensuring more contribution to the economy. Keywords: Growth rate; Instability; Shrimp export DOI: 10.3329/jbau.v8i1.6409 J. Bangladesh Agril. Univ. 8(1): 127-132, 2010